2017
DOI: 10.1007/s10886-017-0856-6
|View full text |Cite
|
Sign up to set email alerts
|

Carnivore Attractant or Plant Elicitor? Multifunctional Roles of Methyl Salicylate Lures in Tomato Defense

Abstract: Synthetic plant volatile lures attract natural enemies, but may have non-target effects due to the multifunctional nature of volatile signals. For example, methyl salicylate (MeSA) is used to attract predators, yet also serves as a signaling hormone involved in plant pathogen defense. We investigated the consequences of deploying MeSA lures to attract predators for tomato (Solanum lycopersicum) defense against herbivores. To understand the spatial distribution of the lure's effect, we exposed tomatoes in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…2b ) after 20 dpi were most likely due to the comparatively large size of the plants, resulting in the limonene dispensers having less effect on whitefly behaviour as the compound diffused to lower concentrations throughout the glasshouse. Although previous studies have shown MeSA to have effects against insects up to four metres away from dispensers (although at high concentrations; Rowen et al ( 2017 )) and some pheromone-based dispensers have effects at eight metres (Braasch and Kaplan 2012 ), the nature of volatile repellence is understood to be dose dependant with higher concentrations having more of an effect (Ben Issa et al 2016 ). Maintaining high concentrations of limonene throughout the canopy may prove key in repelling whiteflies in a commercial glasshouse environment, where tomato plants can reach up to 12 ft. in height.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2b ) after 20 dpi were most likely due to the comparatively large size of the plants, resulting in the limonene dispensers having less effect on whitefly behaviour as the compound diffused to lower concentrations throughout the glasshouse. Although previous studies have shown MeSA to have effects against insects up to four metres away from dispensers (although at high concentrations; Rowen et al ( 2017 )) and some pheromone-based dispensers have effects at eight metres (Braasch and Kaplan 2012 ), the nature of volatile repellence is understood to be dose dependant with higher concentrations having more of an effect (Ben Issa et al 2016 ). Maintaining high concentrations of limonene throughout the canopy may prove key in repelling whiteflies in a commercial glasshouse environment, where tomato plants can reach up to 12 ft. in height.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that spraying of exogenous MeSA has induced this signalling pathway, similar to how methyl jasmonate (MeJA) has been shown to influence the JA signalling pathway (Wu et al 2008 ). There is currently a disparity amongst published literature with some groups showing MeSA to induce JA related defences (Rowen et al 2017 ) and other groups showing induction of SA related defences (Park 2008 ). Whilst we can associate MeSA with induction of SA related defences, which may correlate with increased resistance to whiteflies, the way in which MeSA influences plant signalling pathways remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…urticae most probably obtains this volatile from its host plants (Oku et al 2015). Because SA has been widely recognized as a key factor for predator recruitment by infested plants (i.e., indirect defense) (Mallinger et al 2011;Rodríguez-Saona et al 2011;Kaplan 2012;Rowen et al 2017;Salamanca et al 2017), the question of why a plant volatile exploited by natural enemies as a kairomone is not immobilized/degraded by its potential prey, deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%